The effect of leverage, profitability, earnings per share, and price earning ratio on dividend policy ratio - Mahendra, Putra Wardhana (Universitas Ahmad Dahlan, 2023)
Purpose-The goal of this research is to ascertain how financial ratios, particularly those related to consumer non-cyclicals, affect organizations in relation to dividend policy ratios. Design/Methodology/Approach-Utilizing statistical instruments for multiple regression analysis Eviews is a data processing method that was employed in this study to look at how each of these factors affected the dividend policy ratio. A sample of 19 consumer non-cyclicals sector companies was generated by gathering secondary data from the Indonesia Stock Exchange website. Findings-The results of this investigation demonstrate that the debt equity ratio and price earning ratio both had a negative and positive impact on the dividend policy ratio, however the dividend policy ratio was not positively impacted by return on asset and earnings per share. Research limitations/implications-The results of this study should serve as a reference and source of information for businesses, particularly those in the consumer non-cyclicals sector. These businesses should be aware that a variety of factors, including debt equity ratio, return on asset, earnings per share, and price earning ratio, can impact the dividend policy ratio. This study demonstrates that each of these elements or ratios affects the dividend policy ratio in a unique way. Originality/value-There is still very little research on financial ratios in the consumer non-cyclicals sector. In this study, the ratio allegedly has an impact on the level of dividend policy ratio.